Repetitive DNA probe linked to sex chromosomes in hybrids between Neotropical fish Leporinus macrocephalus and Leporinus elongatus (Characiformes, Anostomidae) - Hashimoto, Diogo Teruo [UNESP]; Parise-Maltempi, Patricia Pasquali [UNESP]; Laudicina, Alejandro; Bortolozzi, Jehud [UNESP]; Senhorini, Jose A.; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Karger, 2009)
Interspecific hybrids of fish can offer important advances in the zootechnical exploration of this animal group. However, hybrids can pose serious biological risks to the environment and natural populations, making genetic characterization and monitoring of hybrids produced in fish culture important concerns. In the present study, individuals of the hybrid 'Piaupara' were characterized by fluorescence in situ hybridization (FISH) using sex-specific probes to differentiate the respective parental contributions from female Leporinus macrocephalus (Piaucu) and male Leporinus elongatus (Piapara). The application of this technique demonstrated a difference in hybridization patterns between males and females of L. elongatus and L. macrocephalus, mainly due to the fact that the NOR-bearing chromosomes of L. elongatus contain some homology with the probe. This allowed us to detect a clear sex-specific distinction of the hybrid 'Piaupara', demonstrating that this technique is well-suited for the characterization of these hybrids. Moreover, this technique offers an important methodological advance for the study of diverse sex chromosome systems of Leporinus, supplying valuable information about the origin and establishment of a recently described sexual system in this genus. Copyright (C) 2009 S. Karger AG, Basel